The Prognosis of Hepatocellular Carcinoma Treated with Sorafenib in Combination with TACE - Kimura, Yusuke (Asian Pac J Cancer Prev, 2020)
OBJECTIVE: Sorafenib have been shown to be effective in the treatment of advanced HCC and has been standard therapy since its release in Japan in 2009 (Llovet et al., 2008; Cheng et al., 2009). However, due to a low response rate, more aggressive combination treatment has been utilized as a multimodal strategy. The present study aimed to determine the efficacy of sorafenib alone and in combination with transarterial chemoembolization (TACE) for the treatment of advanced HCC. METHODS: All patients with unresectable advanced HCC who were prescribed sorafenib at Kanto Rosai Hospital were included in the study. Five-year overall survival (OS) rates were estimated for patients treated with sorafenib alone or in combination with TACE. Multivariate and univariate regression analyses were performed to identify factors affecting OS. Analysis using propensity score matching and inverse-probability weights were also performed. RESULTS: A total of 46 patients were treated with sorafenib up to June 2018. The total sorafenib dose administered was higher in the TACE combination group (70900 mg vs. 24000 mg vs. with sorafenib alone), although the relative dose intensity was lower (11.7% vs. 17.6%, respectively). The 5-year survival prognosis estimated using the Kaplan-Meier method was longer in patients treated with sorafenib in combination with TACE versus sorafenib alone (36.3% vs. 7.7%). Combination with TACE was the only factor associated with improved OS in both univariate and multivariate analysis. Among cases matched by propensity scores the hazard rate for combination with TACE was 0.067 (95% CI 0.091-1.128). CONCLUSION: With an array of therapeutic options currently available, it is important to determine the efficacy of different multimodal strategies, such as sorafenib combined TACE, for patients with unresectable HCC.